The Mughal State, 1526-1750 - Alam, Muzaffar; Subrahmanyam, Sanjay (New Delhi, India: Oxford Univ. Press, 2014)
The Mughal state, has, ever since its existence, exercised a compelling effect on observers. Debates have rage concerning its character and on the nature of the Mughal state. This book brings together some of the key interventions in these debates.